An X-band class-B push-pull power amplifier on a 0.25 ?m SiGe-C process - Çağdaş, Engin; Aniktar, Hüseyin; Savcı, Hüseyin Şerif; Palamutçuoğulları, Osman (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents design of an X-band power amplifier (PA) with Class-B push-pull configuration in 0.25-?m SiGe-C Heterojunction Bipolar Transistor (HBT) BiCMOS process. The PA consists of input balun, driver stage, interstage transformer, output stage and the output transformer. The cascoded structure is chosen to obtain adequate power gain. The simulations show an output power of 21.5 dBm with associated power added efficiency (PAE) of 41% at the operating frequency of 10 GHz. The simulated small signal gain is 21.5 dB with ±1 dB gain flatness from 8 to 12 GHz.
Keywords: HBT; Push-Pull-PA; RFIC; SiGe-C